What I have learnt from helping thousands of people taper off antidepressants and other psychotropic medications. (March 2021) - Framer, Adele
Although psychiatric drug withdrawal syndromes have been recognized since the 1950s – recent studies confirm antidepressant withdrawal syndrome incidence upwards of 40% – medical information about how to safely go off the drugs has been lacking. To fill this gap, over the last 25 years, patients have developed a robust Internet-based subculture of peer support for tapering off psychiatric drugs and recovering from withdrawal syndrome. This account from the founder of such an online community covers lessons learned from thousands of patients regarding common experiences with medical providers, identification of adverse drug reactions, risk factors for withdrawal, tapering techniques, withdrawal symptoms, protracted withdrawal syndrome, and strategies to cope with symptoms, in the context of the existing scientific literature.